Estimation of heterosis and inbreeding depression in okra (Abelmoschus esculentus) - GOSWAMI, AAKANSHA; SINGH, B; SHARMA, ANUBHUTI (The Indian Journal of Agricultural Sciences, 2015)
All parental genotypes of okra [Abelmoschus esculentus (L.) Moench] were sown during the zaid season 2011 at Horticulture Research Centre, Department of Horticulture, Sardar Vallabhbhai Patel University of Agriculture and Technology, Meerut, for developed and maintained for using conventional agronomic practices to keep the crop in good conditions for morphological study. Twenty selected genetically diverse genotypes of okra along with their 51 F1s and 51 F2s population developed in next season through Line x Tester analysis. This experiment was conducted to study the heterosis and inbreeding depression between various economically important traits of okra for the purpose of genetic improvement and their effect in populations. Inbreeding depression was observed for different characters studied in number of crosses. In this best crosses showed 21 crosses early flowering, 40 crosses tallest plant, 29 crosses maximum number of branches, 21 crosses maximum number of nodes per plant, 21 crosses maximum length of first fruiting node, 34 crosses maximum length of internode, 26 crosses maximum length of fruits, 36 crosses maximum width, 39 crosses maximum number of fruits/plant and 32 crosses maximum yield/plant. According to this better fruit yield cross combination BO 2 x Azad Krishna showed maximum inbreeding depression.